An internet-supported school physical activity intervention in low socioeconomic status communities: results from the Activity and Motivation in Physical Education (AMPED) cluster randomised controlled trial - Lonsdale, C.; Lester, A.; Owen, K.; White, R.; Peralta, L.; Kirwan, M.; Diallo, T.; Maeder, A.; Bennie, A.; MacMillan, F.; Kolt, G.; Ntoumanis, Nikos; et al. (BMJ Group, 2017)
Objective: Quality physical education (PE) is the cornerstone of comprehensive school physical activity (PA) promotion programmes. We tested the efficacy of a teacher professional learning intervention, delivered partially via the internet, designed to maximise opportunities for students to be active during PE lessons and enhance adolescents’ motivation towards PE and PA. Methods: A two-arm cluster randomised controlled trial with teachers and Grade 8 students from secondary schools in low socioeconomic areas of Western Sydney, Australia. The Activity and Motivation in Physical Education (AMPED) intervention for secondary school PE teachers included workshops, online learning, implementation tasks and mentoring sessions. The primary outcome was the proportion of PE lesson time that students spent in moderate-to-vigorous physical activity (MVPA), measured by accelerometers at baseline, postintervention (7–8 months after baseline) and maintenance (14–15 months). Secondary outcomes included observed PE teachers’ behaviour during lessons, students’ leisure-time PA and students’ motivation. Results: Students (n=1421) from 14 schools completed baseline assessments and were included in linear mixed model analyses. The intervention had positive effects on students’ MVPA during lessons. At postintervention, the adjusted mean difference in the proportion of lesson time spent in MVPA was 5.58% (p<0.001, approximately 4 min/lesson). During the maintenance phase, this effect was 2.64% (p<0.001, approximately 2 min/lesson). The intervention had positive effects on teachers’ behaviour, but did not impact students’ motivation. Conclusions: AMPED produced modest improvements in MVPA and compares favourably with previous interventions delivered exclusively face-to-face. Online teacher training could help facilitate widespread dissemination of professional learning interventions.